A study of far infrared loop at -5o galactic latitude around pulsar J1627-5547 - Jha, A K; Aryal, B (BIBECHANA, 2017)
We present physical properties of the core region of infrared loop G329-05 which is found to be located within 1o from the pulsar PSR J1627-5547. The loop has 3-fold reduced flux density than its surroundings. In the 100 micron infrared map, a new cavity-like isolated far infrared dust structure of core region (size 0.750 x 0.230 ) is found at R.A. (J2000)= 16h 27m 19.9s & Dec. (J2000) = -56035’14”. This loop is believed to be formed because of high pressure events occurred in the past. The dust color temperature of the core region is found to lie in the range 25.26 ± 0.09 K to 27.91 ± 0.09 K, whereas the value of dust color temperature increased to 36.72 ± 0.18 K for the outer region. The dust color temperature and dust mass distribution maps showed that the low temperature region has greater density as expected. The dust mass of the core region of the loop is found to be 1.67 x 1027 kg i.e. about 0.00835 Mʘ. The core region of the loop is found to be edge-on (i ˃780) whereas the larger structure is faced-on (i =00). Possible explanation of results will be presented. BIBECHANA 15 (2018) 70-76